Application of long gauge sensors on RC structures - Yong, Jun Jordan (Nanyang Technological University, 2024)
Reinforced concrete structures are widely utilized in civil engineering projects due to their durability and strength. However, monitoring their structural health and integrity over time is crucial to ensure safety and prevent potential failures. Long gauge sensors offer a promising solution by providing continuous monitoring of various structural parameters such as strain, temperature, and moisture content along the length of the structure. The primary objective of this study is to determine the most accurate and reliable type of sensor in measuring shear stress by conducting a series of methodical and exhaustive investigation. This study comprises a series of carefully planned laboratory experiments involving the application of various shear forces to specimens of reinforced concrete beams and columns. Various types of sensors are utilized, including Linear Variable Differential Transformers (LVDTs), point gauges, and long gauge sensors (LGS). By applying gradual shear loads and monitoring subsequent responses, our goal is to ascertain the extent of shear stress under varying loading circumstances. Experiments are designed to: Evaluation of LVDTs and Long Gauge Sensors Accuracy for Stress Measurement. This study will assess the precision and reliability of various sensors utilized for measuring stress in structural materials alongside experimental investigations. The findings of this study are expected to significantly enhance the field of civil engineering by providing essential insights into the accuracy of shear stress measurement techniques. Armed with this knowledge, engineers and designers will be empowered to make informed decisions throughout the design and construction phases of concrete structures. Consequently, the built environment will be safer, more reliable, and environmentally sustainable.